Tinjauan Kasus Tentang Dilusi Merek Di Indonesia Dan Thailand - Rika Ratna Permata; tasya safiranita safiranita; Biondy Utama (Fakultas Hukum Universitas Islam Indonesia, 2019)
Theuse of well-known brands without any license, in practice, often intentionally or unintentionally occurs that not only leads violations but also confusion for the public. The use of a brand without any license -but not creating any public confusion -is referred to as brand dilution. This article aims to examine the brand dilution case occurred in Indonesia and Thailand by concerning with two issues: first, to study the case of IKEA vs. IKEMA occurred in Indonesia and the case of STARBUCKS vs. STARBUNG inThailand including in the brand dilution. Second, to study the protection of well-known brands from brand dilution in Indonesia and Thailand. The research used was normative juridical method by means of the statute approach, case approach, analytical approach and comparative approach. The results of this study indicated that first the case of IKEA vs. IKEMA occurred in Indonesia and the case of STARBUCKS vs. STARBUNG is categorized as the brand dilution in consideration to the brand use that has a similarity to well-known brands. Though it has a different class of goods and/or services, it can eliminate the uniqueness of the famous brand. Second, both Indonesia and Thailand have not specifically regulated the brand dilution. Indonesia is only based on the overall protection on equality and/or equality in principle, while Thailand is only based protection on confusion.